President's Message - Socha, Linda; McLeod, Bonnie (Operating Room Nurses Association of Canada Journal, 2009)
It’s hard to imagine my term as President is nearing its end! Looking back at my first message in CORNJ, my enthusiasm and nervous anticipation were clearly evident. I am happy to say the feelings never swayed – every opportunity and challenge presented meant potential for organizational growth. Armed with that knowledge, and with the foundation laid by those before me, it has been an honour and a privilege to contribute to the ongoing development of ORNAC.